2020
DOI: 10.3390/ijerph17020514
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Utilization of Inpatient Services for Middle-Aged and Elderly Rural Females in Less Developed Regions of China

Abstract: The aim of this study is to understand the utilization of inpatient services and its contributing factors among middle-aged and elderly females (MAEF) in less developed rural regions. Five surveys were conducted between 2006 and 2014 with rural residents of Jiangxi by stratified cluster random sampling. Participant females included only those who were aged 45 and above. Complex sampling logistics analysis was performed to analyze the effect of three factors on inpatient service. Complex sampling logistics regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 44 publications
(54 reference statements)
6
4
0
Order By: Relevance
“…This phenomenon is consistent with our hypothesis and is also consistent with the other studies among the Fig. 2 The rate of annual inpatient health service utilization from 2011 to 2018 elderly in China [16,29]. The medical security system is known to have a positive impact on IHSU; accordingly, the increasing rate of IHSU may be related to the massive increase in demand for medical care following the introduction of medical security systems [30,31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This phenomenon is consistent with our hypothesis and is also consistent with the other studies among the Fig. 2 The rate of annual inpatient health service utilization from 2011 to 2018 elderly in China [16,29]. The medical security system is known to have a positive impact on IHSU; accordingly, the increasing rate of IHSU may be related to the massive increase in demand for medical care following the introduction of medical security systems [30,31].…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have confirmed that some demographic or socioeconomic determinants will affect people's use of inpatient services [32][33][34]. In our study, age, chronic diseases, economic status and lifestyle were found to be associated with the IHSU, conforming to previous study analyzing health inequity [29]. First of all, age and chronic diseases had positive elasticity and pure percentage contribution to CI, which indicated older and having chronic diseases were significantly associated with the occurring of IHSU.…”
Section: Discussionsupporting
confidence: 88%
“…This finding is consistent with recent research showing somewhat greater reductions in mortality related to adequate access to healthcare in rural settings than in urban settings [5]. Although the healthcare system was improved in rural China in 2000-2015 [41], these areas continued to have healthcare programs that were less adequate than those in urban areas [25,35,42]. It has been shown that financial barriers are often major obstacles for acquiring care in rural areas [5]; largely because of low income (and few pensions), high out-of-pocket costs, and high medical co-payments [43].…”
Section: Discussionsupporting
confidence: 89%
“…Middle-aged and elderly females with chronic diseases and non-labor females have a higher probability of getting hospitalized in accordance with a study conducted in a Chinese Province [ 16 ].…”
supporting
confidence: 85%